Conversational Analysis of Adjacency Pairs in “The Murder of Roger Ackroyd” Novel by Agathe Christie - Hadeel Al-Sa’adoon; Baidaa Al-Zubaidy (مجلة الآداب, 2024)
This study delves into the pivotal role of adjacency pairs (APs) as fundamental units in conversation analysis, with a specific focus on their application in the context of detective novels, notably exemplified in the works of Agatha Christie. APs, consisting of a first pair part (FPP) and a second pair part (SPP) are crucial tools in understanding the dynamics of dialogue, as they reveal underlying structures and meanings within conversations. Thus, the present study aims to determine the most dominant pattern of adjacency pairs which are utilized in shaping the dialogue in Christie’s works; and to investigate how Christie employs a specific adjacency pair pattern to impart a distinctive touch to her detective narratives. Depending on these aims, the following hypotheses are proposed: Firstly the superiority of these adjacency pairs is given to (Question–Answer/ Clarification) pattern. Secondly, the use of the (Announcement – Acceptance / Denial) pattern is an unexpected way to identify the criminal of the novel. In order to test the validity of these hypotheses. The novel (The Murder of Roger Ackroyd) by Agatha Christie is analyzed by adopting eclectic models i.e. Coulthard (1985), Clark (1996), Schegloff (2007) and Paltridge (2012). The results of the analysis are set following mixed methods using quantitative and qualitative methods The present study concludes that writers can leverage Agatha Christie's adept use of adjacency pairs employing (Question-Answer), to elevate narrative impact. Screenwriters adapting Christie's works for visual media can benefit from understanding the significance of these pairs in guiding dialogue construction for cinematic portrayal. These insights can be incorporated into literature or linguistics courses as case studies, serving as teaching tools to illustrate effective linguistic devices and deepen comprehension of narrative strategies.